2012
DOI: 10.7166/5-1-423
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of an Automated Visual Inspection System

Abstract: An automated visual inspection system is not the panacea that it is made out to be. There are many pitfall s for the unwary company wi sh i ng to implement such an . inspection system.The major advantages and disadvantages are discussed in this paper. This will increase the probability that anyone installing a visual inspection station will obtain a successful system that meets their needs. OPSOMMING'n Outomatiese visuele inspeksiestelsel is nie die wonderwerk wat die industrie verwag het nie. Daar is probleem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A review of the industrial vision system can be found in the studies [2][3][4][5][6][7][8]. Figure 1 presents the flow of product in an assembly line where the raw material is converted to a finished product in different steps, and after the finished product is available, a set of the inspection system is initiated to inspect the quality of the finished product.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the industrial vision system can be found in the studies [2][3][4][5][6][7][8]. Figure 1 presents the flow of product in an assembly line where the raw material is converted to a finished product in different steps, and after the finished product is available, a set of the inspection system is initiated to inspect the quality of the finished product.…”
Section: Introductionmentioning
confidence: 99%